Knowledge internalization in pair programming practices - Md Rejab, Mawarny; Omar, Mazni; Ahmad, Mazida (Universiti Utara Malaysia Press, 2013)
Pair programming practice has been widely used as a pedagogical approach in educational setting specifically in the programming course.Most pair programming studies agree that this practice can foster knowledge sharing among students.However, the studies do not highlight knowledge internationalization during pair programming practice. Therefore, this paper will discuss knowledge internalization based on tacit knowledge that occurs from knowledge sharing activities in pair programming practices.This is achieved by employing the process of Socialization, Externalization, Combination, and Internalization (SECI) in the form of learning, thinking and decision-making skills among the students.119 participants were actively engaged in the pair programming practice in this study.The participants were required to answer questionnaires, which were adapted from the SECI model to suit the educational context. Statistical t-test was used to analyse the data.The results showed that pair programming was able to promote knowledge internationalization in the thinking process.This study contributes to a better understanding of important knowledge sharing activities to construct student’s skills during the internalization process through pair programming. Future works will be focused into a rigorous theoretical framework for constructing tacit knowledge among the students in pair programming environment.